KEPUASAN ANGGOTA TERHADAP PERAN KELOMPOK DALAM PELAKSANAAN PROGRAM PEMANFAATAN PEKARANGAN DI KAWASAN PERKOTAAN (STUDI KASUS DI KELOMPOK WANITA TANI KENTAGOR MANDIRI KOTA BOGOR) - Alfayanti, Alfayanti; Baga, Lukman M; Yusalina, Yusalina (Jurnal AGRISEP, 2021)
The Sustainable Home Food Area (KRPL) is the yard utilization programs that empowers community in the form of groups, one of which is Woman Farmers Group (KWT). The sustainability of program implementation is dependent on the active participation of members which influenced by satisfaction with the role of the group. This study aims to analyze the levels and attributes that determine member satisfaction to the role of the group in implementation the KRPL program. The research was conducted at KWT Kentagor Mandiri Kencana Village, Tanah Sereal District, Bogor City in December 2019-June 2020. Sample amount of 34 people were determined by census method. The data used are primary and secondary data. Primary data comes from interviews with KWT members while secondary data is obtained from literature studies and documents of related agencies. The level of member satisfaction with the group's role in implementing the yard utilization program was analyzed using the Customer Satisfaction Index (CSI) approach, while the determining factors were determined using a quadrant analysis on the Importance Performance Analysis (IPA).The results show that the members are satisfied with the performance of the group's role in implementation the KRPL program as indicated by the CSI index value of 0.80. There are five attributes that determine members' satisfaction with the role of the group in implementation the KRPL program, namely planning learning needs, arranging group task division, planning collaborative activities, planning the types of foodstuffs to be cultivated and facilitating the availability of seeds